The art of youthful restraint: negotiating youth-adult relations in digital media literacy. Issue 2 (3rd April 2021) - Jimenez, Carlos; Clark, Lynn Schofield; Kennedy, Heather; Nisle, Stephanie; Engle, Corey; Matyasic, Savahanna; Anyon, Yolanda
ABSTRACT: Scholarship on youth digital media literacy programs has focused on how adults practice restraint as a means of allowing young people to exercise agency in decision-making experiences. Yet youth also practice restraint, as we found in a digital storytelling program involving 16 early adolescents (ages 11–14) from economically precarious communities who worked with 18 adult mentors trained in discussing systemic and racial injustices in the context of trauma-informed practices. Building on a framework of critical youth studies, our ethnographic data reveals how youth deployed their own version of restraint that is simultaneously defensive and agentive . We argue that this is a form of empowerment that needs to be better understood in the contexts of actual practices of youth/adult media co-production, and in relation to support for the development of critical, participatory and collaborative, and expressive competencies (Mihailidis, P., and B. Thevenin. 2013. "Media Literacy as a Core Competency for Engaged Citizenship in Participatory Democracy." American Behavioral Scientist 57 (11): 1611–1622). Restraint is thus presented as a strategy of empowerment that youth develop in relation to digital media literacy and youth voice, especially for young people from populations historically marginalized and frequently misunderstood in media and in public life.